Towards the Forest Virome: High-Throughput Sequencing Drastically Expands Our Understanding on Virosphere in Temperate Forest Ecosystems - Artemis Rumbou; Eeva J. Vainio; Carmen Büttner (Microorganisms, 2021)
Thanks to the development of HTS technologies, a vast amount of genetic information on the virosphere of temperate forests has been gained in the last seven years. To estimate the qualitative/quantitative impact of HTS on forest virology, we have summarized viruses affecting major tree/shrub species and their fungal associates, including fungal plant pathogens, mutualists and saprotrophs. The contribution of HTS methods is extremely significant for forest virology. Reviewed data on viral presence in holobionts allowed us a first attempt to address the role of virome in holobionts. Forest health is dependent on the variability of microorganisms interacting with the host tree/holobiont; symbiotic microbiota and pathogens engage in a permanent interplay, which influences the host. Through virus–virus interplays synergistic or antagonistic relations may evolve, which may drastically affect the health of the holobiont. Novel insights of these interplays may allow practical applications for forest plant protection based on endophytes and mycovirus biocontrol agents. The current analysis is conceived in light of the prospect that novel viruses may initiate an emergent infectious disease and that measures for the avoidance of future outbreaks in forests should be considered.